The legal effects of tax contracts and their role in increasing revenues - Assistant Teacher Duaa Kazem Tarish; Assistant Teacher Russell Baqer Taher (The college of law and political science journal, 2023)
The importance of this study lies in shedding light on the tax penalty and clarifying its role in increasing the financial receipts entering the public treasury when it is imposed on the violating taxpayer, Since the tax is a financial obligation to be cut compulsorily and without consideration for the purpose of achieving the general objectives, The state has obligated all individuals to pay their share in it, each according to his financial ability, within the framework of achieving social and financial justice, However, these efforts may be surrounded by the failure of some taxpayers to pay the tax debt by concealing their activities in whole or in part to withhold their real revenues from paying the tax due on them.Therefore, since imposing a tax is only by law in accordance with constitutional guarantees, and since the main pillar of respect for the law is the penalty or punishment for violating it, The tax laws organized a set of penalties imposed on the perpetrator of the tax crime, including penalties restricting freedom, including financial penalties whose imposition helps to increase the financial outcome of the state.